2006
DOI: 10.1073/pnas.0509379103
|View full text |Cite
|
Sign up to set email alerts
|

On the origin and highly likely completeness of single-domain protein structures

Abstract: The size and origin of the protein fold universe is of fundamental and practical importance. Analyzing randomly generated, compact sticky homopolypeptide conformations constructed in generic simplified and all-atom protein models, all have similar folds in the library of solved structures, the Protein Data Bank, and conversely, all compact, single-domain protein structures in the Protein Data Bank have structural analogues in the compact model set. Thus, both sets are highly likely complete, with the protein f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
178
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(202 citation statements)
references
References 37 publications
13
178
2
Order By: Relevance
“…A more recent study using computational sampling of homopolypeptide conformations suggested further that the current repertoire of globular protein folds is nearly complete in its coverage of all physically possible compact folds [286]. However, studies by three other groups have found instead that the current fold repertoire represents only a small fraction of all possible folds [287 -289].…”
Section: Applications Of Biophysics-based Models To Understand Proteimentioning
confidence: 99%
“…A more recent study using computational sampling of homopolypeptide conformations suggested further that the current repertoire of globular protein folds is nearly complete in its coverage of all physically possible compact folds [286]. However, studies by three other groups have found instead that the current fold repertoire represents only a small fraction of all possible folds [287 -289].…”
Section: Applications Of Biophysics-based Models To Understand Proteimentioning
confidence: 99%
“…Consistent with this notion, it was estimated that there are about 1,000 structural folds in protein domains (10). Recent studies suggest that the library of single-domain protein structures is likely complete, continuous, and above the percolation threshold, largely due to the packing of compact, hydrogen-bonded secondary structural elements (11)(12)(13). Because many structural properties of real proteins are reproduced by a library of compact, hydrogen-bonded homopolypeptide structures, evolution is not necessary to explain these features.…”
mentioning
confidence: 54%
“…Second, it is known that physical constraints limit the total number of distinct structural folds for protein domains (9,12). Obviously, the same constraints may restrict the valid ways of packing pairs of proteins; this is the second reason for detecting structural similarity between unrelated interfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Arguments were made that the PDB is indeed complete (22,23) with the current thousands of distinct folds. This argument further supports the creation of a comprehensive model of protein structure space and their sequence capacities and the progressive refinement of this model.…”
mentioning
confidence: 99%